2007
DOI: 10.1029/2006jd007711
|View full text |Cite
|
Sign up to set email alerts
|

Mesopause structure from Thermosphere, Ionosphere, Mesosphere, Energetics, and Dynamics (TIMED)/Sounding of the Atmosphere Using Broadband Emission Radiometry (SABER) observations

Abstract: [1] Thermosphere, Ionosphere, Mesosphere, Energetics, and Dynamics (TIMED)/ Sounding of the Atmosphere Using Broadband Emission Radiometry (SABER) temperature observations are used to study the global structure and variability of the mesopause altitude and temperature. There are two distinctly different mesopause altitude levels: the higher level at 95-100 km and the lower level below $86 km. The mesopause of the middle-and high-latitude regions is at the lower altitude in the summer hemisphere for about 120 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
99
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 31 publications
31
99
2
Order By: Relevance
“…It is obvious in Figure 1 that the AO and SAO are the most prominent zonal mean oscillations in the middle atmosphere, and their morphologies are in agreement with previous studies (e.g., [3,4]). In addition, the three-year oscillation signal, which is significant as well as the QBO and SAO, especially at around 45 km over the equatorial region, has attracted our attention.…”
Section: Lomb-scargle Spectral Analysissupporting
confidence: 79%
“…It is obvious in Figure 1 that the AO and SAO are the most prominent zonal mean oscillations in the middle atmosphere, and their morphologies are in agreement with previous studies (e.g., [3,4]). In addition, the three-year oscillation signal, which is significant as well as the QBO and SAO, especially at around 45 km over the equatorial region, has attracted our attention.…”
Section: Lomb-scargle Spectral Analysissupporting
confidence: 79%
“…PMC altitudes are sensitive to temperature but also to other variable fields such as water vapor and vertical wind. Xu et al (2007a) found similar differences in the mesopause height determined from SABER temperature measurements. Hervig and Siskind (2006) found larger differences in mean summer temperature at 65-70°in HALOE data; the SH was warmer by 3-6 K throughout the mesosphere.…”
Section: Hemispheric Differencessupporting
confidence: 68%
“…1). However, in the summer high latitudes, the mesopause temperature is much lower, and its altitude is lower (von Zahn et al 1996;Xu et al 2007a). The global low temperature at 95-100 km is due to the radiative balance there.…”
Section: Zonal Mean Temperature and Windsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several space-borne instruments like the Microwave Limb Sounder (MLS) on the Aura satellite; Atmospheric Chemistry Experiment -Fourier Transform Spectrometer (ACE-FTS) on SciSat-1; Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) and SCIAMACHY (Scanning Imaging Absorption Spectrometer for Atmospheric Chartography) on Environmental Satellite (ENVISAT); Solar Occultation for Ice Experiment (SOFIE) on the AIM satellite; Optical, Spectroscopic, and Infrared Remote Imaging System (ORISIS) on the Odin satellite; the Cryogenic Infrared Spectrometers and Telescopes for the Atmosphere (CRISTA) satellite instrument, and Sounding of the Atmosphere by Broadband Emission of Radiation (SABER) on-board the TIMED mission satellite have also contributed immensely to our knowledge of the temperature field of the MLT region (von Savigny et al, 2004;Scheer et al, 2006;Xu et al, 2007;Mulligan and Lowe, 2008;French and Mulligan, 2010;Sheese et al, 2011;García-Comas et al, 2012, 2014and references cited therein).…”
Section: Introductionmentioning
confidence: 99%